A modified dynamic stiffness calculation method of rubber isolator considering frequency, amplitude and preload dependency and its application in transfer path analysis of vehicle bodies. (April 2021) - Xia, Erli; Cao, Zhenglin; Zhu, Xuewu; Qiu, Sawei; Xue, Zhigang; He, Hong; Li, Luoxing
Abstract: An accurate prediction of the dynamic stiffness of the rubber isolator is critical to vehicle noise, vibration, and harshness performance. However, it is rather difficult due to the fact that it is simultaneously influenced by their application environment factors such as frequency, amplitude, and preload, etc. So far, related studies are still few. In the present study, taking the typically used chassis rubber bushing as the research object, a series of dynamic stiffness tests for rubber bushings was conducted under different frequencies, amplitudes, and preloads conditions. The Zener model was adopted to consider the frequency dependence, and an operation coefficient was introduced to quantify the amplitude and preload dependence. In order to obtain the actual dynamic stiffness of such rubber isolator, a modified calculation method considering the frequency, amplitude, and preloads dependence was proposed. The effectiveness of the proposed method was validated through comparing the accelerations synthesized by the transfer path analysis method with experimentally measured values. Compared to the traditional approach, the response can be more accurately calculated by the proposed method. It was further applied in solving the abnormal door vibration problem in a typical SUV. The vibration contribution analysis shows that the reasons for the door vibration problem caused by excessive transmitted forces at the rear stabilizer bar bushing in the x -direction and z -direction. A solution based on the analysis of the influence of corresponding bushing dynamic stiffness on target acceleration was therefore adopted to solve the abnormal door vibration problem effectively.